2015
DOI: 10.1007/s10803-015-2575-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Competence and Loneliness Among Young Children with ASD: Child, Parent and Teacher Reports

Abstract: Perceived loneliness and social competence were assessed for 127 children with ASD without comorbid ID, 4-7 years old, through child self-report. Using an abbreviated version of the Loneliness and Social Dissatisfaction Questionnaire (LSDQ; Cassidy and Asher in Child Dev 63:250-365, 1992), the majority of children reported friendships, yet a considerable proportion also reported social difficulties. Factor analysis of the abbreviated LSDQ identified three factors, which were significantly associated with paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 38 publications
1
34
0
2
Order By: Relevance
“…Cook et al (2017) found that several adolescent girls try to conceal their autism characteristics to make friends. Teacher-student conflicts were found to exacerbate feelings of loneliness in students with HFA (Zeedyk et al, 2016). According to Zeedyk et al (2016): "Teachers may not be aware of the degree to which their behaviours and attitudes toward children with ASD impact both what the child with ASD thinks about him/herself, and possibly how peers view him/her" (p. 446).…”
Section: Deficits In Social Skills Impact Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cook et al (2017) found that several adolescent girls try to conceal their autism characteristics to make friends. Teacher-student conflicts were found to exacerbate feelings of loneliness in students with HFA (Zeedyk et al, 2016). According to Zeedyk et al (2016): "Teachers may not be aware of the degree to which their behaviours and attitudes toward children with ASD impact both what the child with ASD thinks about him/herself, and possibly how peers view him/her" (p. 446).…”
Section: Deficits In Social Skills Impact Relationshipsmentioning
confidence: 99%
“…The lack of educator practice guidelines and training in teacher programs have contributed to the lack of implementation of appropriate interventions (Lauderdale-Litten & Brennan, 2018;Marder & Fraser, 2012). Regular education teachers have been singled out as the inclusion educators most likely to experience burnout (Boujut, Dean, Grouselle, & Cappe, 2016), most likely in need of training (Lauderdale-Litten & Brennan, 2018) and, yet, potentially, the most critical to fostering the student's sense of belonging (Zeedyk et al, 2016). Public schools face a multitude of challenges in implementing appropriate evidence-based interventions such as: lack of funding, lack of knowledge, lack of training, lack of support, and lack of time (Grindle et al, 2009;Miller, 2017;Owens et al, 2014).…”
Section: Evidence-based Practices For Social Skillsmentioning
confidence: 99%
“…A number of studies have demonstrated that students with disabilities, such as mild intellectual disabilities, learning disabilities, and autism in inclusive settings reported more loneliness and less satisfaction in peer relationships compared to their typically developing peers (Heiman & Margalit, 1998;Jobe & White, 2007;Pavri & Luftig, 2001;Pavri & Monda-Amaya, 2000;Valas, 1999;Williams & Asher, 1992). However, a limited number of studies have examined the relationships between loneliness and self-concept (Fujiki, Brinton, & Todd, 1996), loneliness and social skills (Zeedyk, Cohen, Eisenhower, & Blacher, 2015), and loneliness and problem behaviors (Howell, Hauser-Cram, & Kersh, 2007). Moreover, only a few studies in Turkey have investigated the academic achievements and social and behavioral characteristics of SEN students in inclusive classrooms (Girli, 2013;Kanay & Girli, 2008;Sucuoglu & Ozokcu, 2005), and no studies have focused on the relationship of loneliness with self-concept, social skills, or problem behaviors of children with special needs except one study examined the relationship between the loneliness and social status of SEN students (Bakkaloglu, 2010).…”
mentioning
confidence: 99%
“…I flere studier rapporterer barn og ungdommer med autisme større grad av ensomhet enn sine jevnaldrende (Bauminger & Kasari, 2000;Bauminger et al, 2003;Lasgaard, Nielsen, Eriksen & Goossens, 2010;Locke et al, 2010;Zeedyk, Cohen, Eisenhower & Blacher, 2016). I intervju med ungdommer med autisme fant Locke et al (2010) at de ofte bedømte seg selv negativt med tanke på egenskaper de trodde var nødvendige i et vennskap (for eksempel: 'for å vaere en god venn må man vaere tålmodig'.…”
Section: Barnas Erfaringer Med å Vaere Inkludertunclassified